2016
DOI: 10.1364/ome.6.001003
|View full text |Cite
|
Sign up to set email alerts
|

Influence of alignment layers on crystal growth of polymer-stabilized blue phase liquid crystals

Abstract: The feature that devices based on blue phase liquid crystals (BPLCs) is free of alignment layers. However, the alignment layers could affect the morphologies of BPLC-devices as well as the electro-optical properties. In this paper, we investigate the influence of alignment layers to crystal growth of polymer-stabilized blue phase liquid crystals (PS-BPLCs). Without alignment layer, PS-BPLCs experiences both homogeneous nucleation and heterogeneous nucleation, and the morphology appears in random crystal orient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
1
12
0
1
Order By: Relevance
“…These authors also observed that nucleation is mediated by the chemical interactions and anchoring energy between the LC molecules and the surface (29). Phase transitions between BPs have been found to be first order.…”
mentioning
confidence: 88%
“…These authors also observed that nucleation is mediated by the chemical interactions and anchoring energy between the LC molecules and the surface (29). Phase transitions between BPs have been found to be first order.…”
mentioning
confidence: 88%
“…Учитываются условия на границе раздела слоев в сложной конструкции ЖК-ячейки, условия питания и облучения ЖК-мезофазы, способы ориентирования ЖК-молекул, а также модификация мезофазы разного рода частицами, как то: фуллеренами, квантовыми точками, шунгитами, оксидами графена, J-агрегатами, др. [10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Вполне понятно, что как процесс сенсибилизации ЖК, так и граничные условия существенно влияют на физические свойства ЖК, в том числе на временны́е параметры устройств на их основе, характеризующие реакцию и релаксацию мезофазы.…”
Section: Introductionunclassified
“…Despite the blue phase was discovered already in 1888, by Austrian botanist Reinitzer [5], its properties were described years later at the end of 20th century. Currently the new technology of observation and analysis allow to get more information about structure of BP domains, their growth [6][7][8], optical properties and potential applications [9][10][11][12][13][14][15][16][17][18]. The temperature range of BP appearance can be extended, by addition of bimesogenic molecules or nanoparticles [19][20][21] and stabilized Email address: martef@if.pw.edu.pl (M. M. Sala- Tefelska) by using a polymer [22].…”
Section: Introductionmentioning
confidence: 99%